2012
DOI: 10.4103/1119-3077.97315
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors of ante-partum hemorrhage among Arab women in an economically fast growing society

Abstract: Qatar has a high prevalence of APH. Poor education, family history of hypertension, G6PD and Down's syndrome were found to be significantly associated with increased risk of APH in Qatar. Neonates of APH are at significantly increased risk of adverse outcome. Thus it is essential that obstetricians are alerted to these risk factors for early detection and to decrease the negative effects of APH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 0 publications
2
17
0
2
Order By: Relevance
“…The overall prevalence in a study from Qatar was found to be 15.3%[7] and poor education, family history of hypertension, G6PD, and Down's syndrome were found to be significantly associated with increased APH in that study. [7] However, in a study from Osun, South-Western Nigeria, the prevalence was 1.5% and the major cause of antepartum hemorrhage was found to be placenta previa followed by abruption and lastly by unknown causes.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The overall prevalence in a study from Qatar was found to be 15.3%[7] and poor education, family history of hypertension, G6PD, and Down's syndrome were found to be significantly associated with increased APH in that study. [7] However, in a study from Osun, South-Western Nigeria, the prevalence was 1.5% and the major cause of antepartum hemorrhage was found to be placenta previa followed by abruption and lastly by unknown causes.…”
Section: Introductionmentioning
confidence: 94%
“…[7] However, in a study from Osun, South-Western Nigeria, the prevalence was 1.5% and the major cause of antepartum hemorrhage was found to be placenta previa followed by abruption and lastly by unknown causes. [8] In Lagos, Nigeria, an incidence of 3.5% was reported and placenta previa constituted 58.4% of the cases, while placental abruption was a factor in 35.6%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obstetric hemorrhage is a leading cause of fetomaternal mortality and morbidity in Sub-Saharan Africa [4]. Placenta previa has further been linked to maternal hypovolemia, anemia, and long hospital stay, as well as adverse fetal outcomes such as low birth weight, congenital abnormalities, stillbirth, and early neonatal death [5–9]. …”
Section: Introductionmentioning
confidence: 99%
“…While the precise etiology of placenta previa is not known, previous studies have elucidated predictive factors such as high maternal age, twin pregnancies, previous Caesarean section, previous uterine scar, grand multiparity, malpresentation, and diabetes mellitus [5, 711]. …”
Section: Introductionmentioning
confidence: 99%